2020
DOI: 10.3390/biom10040574
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional Changes in Parameters Related to Sulfur Metabolism in Frog Tissues Exposed to Heavy Metal-Related Stress

Abstract: The investigations showed changes of the cystathionine γ-lyase (CTH), 3-mercaptopyruvate sulfurtransferase (MPST) and rhodanese (TST) activity and gene expression in the brain, heart, liver, kidney, skeletal muscles and testes in frogs Pelophylax ridibundus, Xenopus laevis and Xenopus tropicalis in response to Pb 2+ , Hg 2+ and Cd 2+ stress. The results were analyzed jointly with changes in the expression of selected antioxidant enzymes (cytoplasmic and mitochondrial superoxide dismutase, glutathione peroxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…Taking into consideration the level of sulfane sulfur-containing compounds in the tested cell lines ( Table 5 ), we observed that their value was in the range: 41 nmole/mg protein (the SH-SY5Y cells); 190 nmole/mg protein (the MNuMG cells). In cells, sulfane sulfur-containing compounds are produced in the non-oxidative metabolism of cysteine [ 36 , 39 ]. In all the tested lines, the obtained values of the cysteine level were low and equaled on average ca.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into consideration the level of sulfane sulfur-containing compounds in the tested cell lines ( Table 5 ), we observed that their value was in the range: 41 nmole/mg protein (the SH-SY5Y cells); 190 nmole/mg protein (the MNuMG cells). In cells, sulfane sulfur-containing compounds are produced in the non-oxidative metabolism of cysteine [ 36 , 39 ]. In all the tested lines, the obtained values of the cysteine level were low and equaled on average ca.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of disulfide protects them against irreversible oxidation, as S-S bonds can be reduced by the thioredoxin/thioredoxin reductase (EC 1.8.1.9) system or the glutathione/glutharedoxin/glutathione reductase (EC 1.8.1.7) systems. Thus, MPST, as well as other two sulfurtransferases-thiosulfate sulfurtransferase (TST, also known as rhodanese, EC 2.8.1.1, Figure 6) and cystathionine γ-lyase (CTH, EC 4.4.1.1, Figure 6), partly contribute to maintaining the redox homeostasis and serves as an antioxidant protein [101,[103][104][105][106]. Their action helps to maintain homeostasis of the sulfane sulfur-containing compounds levels in cells.…”
Section: Effects Of Gags/hs Accumulation On Sulfur Metabolismmentioning
confidence: 99%
“…Высокие коэффициенты накопления обусловлены, по всей видимости, содержанием в исследованных водных объектах в биодоступной форме цинка, железа, меди (гидрокарбонатные формы, гидроксокомплексы), хрома (хромат анионы), марганца (сернокислые, хлористые и азотнокислые соли). Выявленные межвидовые различия могут быть связаны с особенностями сред обитания близкородственных видов, с присутствием в их рационе пи- Из литературы известно, что, попадая в организм, металлы практически не подвергаются каким-либо существенным превращениям, включаются в биохимический цикл и крайне медленно покидают его (Лобанова, 2008;Моисеенко, 2008;Kaczor-Kami et al, 2020). Находясь в тканях и органах в виде комплекса с белками, аминокислотами и другими биологически активными соединениями, металлы способны вызывать нарушение функций, отравление или гибель организма.…”
Section: результаты и их обсуждениеunclassified